Bilateral breast cancer: the role of mammography and ultrasonography in early detection - Lekamnuaypon, Onthira; Kongmebhol, Pailin; Muttarak, Malai; Sukhamwang, Neelaya (Biomedical Sciences and Clinical Medicine, 2024)
Purpose To determine the role of mammography and ultrasonography (US) in the early detection of bilateral breast cancer and ascertain its clinical, imaging, and pathologic features. Materials and methods The pathologic and breast imaging records were searched from Maharaj Nakorn Chiang Mai Hospital between January 2009 and December 2011 to identify patients diagnosed with bilateral breast cancer. The clinical features, method of diagnosis, time interval between development of the fi rst and second breast cancer, histologic type, staging of the tumor, mammography, and US findings of patients diagnosed bilateral breast cancer were analyzed. Results Seven hundred and seventy one patients were pathologically diagnosed breast cancer. Of these, 20 (2.6%) had bilateral breast carcinoma. However, only 19 patients aged 35-76 years (mean, 56.6 years) had imaging studies that constituted the basis of this study. Among them, seven had synchronous and 12 metachronous bilateral breast cancer. The interval to detection of the second cancer ranged from 17 to 324 months (mean, 111.7 months). Of the seven patients with synchronous cancer, five contralateral cancers were presented with a palpable mass detected from physical examination, mammography and US, with one cancer detected by both mammography and US, and the other by US alone. Of the 12 patients with metachronous carcinoma, one had pathologically proved multicentric contralateral breast cancer. Thus, there were 13 contralateral cancers in this group. Of the 12 patients with metachronous cancer, six presented with a palpable mass and six came to the hospital for mammographic screening. Six of the 13 cases of contralateral cancers were detected by physical examination, mammography and US, six by both mammography and US, and one by US alone. Pathologic findings of the lesions were ductal carcinoma in situ in 4, invasive ductal carcinoma in 14, invasive papillary carcinoma in 1 and invasive lobular carcinoma in 1. Stages of tumors in asymptomatic patients were stage 0 in 3, stage I in 4 and stage III in 1, and in patients with a palpable mass; stage I in 4, stage II in 4 and stage III in 3. Conclusion Contralateral breast cancers in bilateral breast cancer detected by mammography and US were less advanced than those found by physical examination.